Chromosomal Integration of Huge and Complex blaNDM-Carrying Genetic Elements in Enterobacteriaceae - Luo, Xinhua; Yin, Zhe; Zeng, Lijun; Hu, Lingfei; Jiang, Xiaoyuan; Jing, Ying; Chen, Fangzhou; Wang, Dongguo; Song, Yajun; Yang, Huiying; Zhou, Dongsheng (Frontiers in Cellular and Infection Microbiology, 2021)
In this study, a detailed genetic dissection of the huge and complex blaNDM-carrying genetic elements and their related mobile genetic elements was performed in Enterobacteriaceae. An extensive comparison was applied to 12 chromosomal genetic elements, including six sequenced in this study and the other six from GenBank. These 12 genetic elements were divided into five groups: a novel IME Tn6588; two related IMEs Tn6523 (SGI1) and Tn6589; four related ICEs Tn6512 (R391), Tn6575 (ICEPvuChnBC22), Tn6576 and Tn6577; Tn7 and its derivatives Tn6726 and 40.7-kb Tn7-related element; and two related IMEs Tn6591 (GIsul2) and Tn6590. At least 51 resistance genes, involved in resistance to 18 different categories of antibiotics and heavy metals were found in these 12 genetic elements. Notably, Tn6576 carried another ICE Tn6582. In particular, the six blaNDM-carrying genetic elements Tn6588, Tn6589, Tn6575, Tn6576, Tn6726, and 40.7-kb Tn7-related element contained large accessory multidrug resistance (MDR) regions, each of which had a very complex mosaic structure that comprised intact or residual mobile genetic elements including insertion sequences, unit or composite transposons, integrons and putative resistance units. Core blaNDM genetic environments manifested as four different Tn125 derivatives and, notably, two or more copies of relevant Tn125 derivatives were found in each of Tn6576, Tn6588, Tn6589, and 40.7-kb Tn7-related element. The huge and complex blaNDM-carrying genetic elements were assembled from complex transposition and homologue recombination. Firstly identified were eight novel mobile elements, including three ICEs Tn6576, Tn6577 and Tn6582, two IMEs Tn6588 and Tn6589, two composite transposons Tn6580a and Tn6580b, and one integron In1718.